(untitled) (Journal of Social Sciences Review, 2022)
A Latin word Tolerantia is introduced in English language as Tolerance means Patience or endurance has increasingly caught the attention of researchers and scholars in the present times. This research aims at exploring the major reasons related to the difference of tolerance levels of students learned from Madrassa and University. Secondly it sorts out the core differences and address them equally to find a way for their resolution through casual comparative research design. Data were collected conveniently from 300 respondents having ages ranged from 24 to 30 years from both disciplines (Madrassa & University) through five point likert scale questionnaire comprising of 29 items. For checking the reliability of the scale, a pilot study was conducted and .674 Cronbach’s Alpha was found. Data were analyzed on independent sample t-test through SPSS. The study found a significant difference between the tolerance level of students learned from Madrassa and University. The tolerance level of students learned from Madrassa was very low.